Laser modeling a numerical approach with algebra and calculus - Csele, Mark Steven (CRC Press, 2014)
The approach taken in this book is simple present laser theory in an understandable way and one that can be applied immediately, and numerically, to real laser systems. With that in mind, the approach in this text is to present each theory along with a real, solved example--in most cases, based on commercial lasers. As a professor of laser science, I am fortunate to have a lab equipped with many different types of lasers; many of those lasers are included here in examples. In making the theory "accessible," both a calculus-based and an algebraic approach are shown in tandem; a prime example of this is the presentation of both the calculus-based Rigrod model and an algebra-based model for the prediction of various laser parameters in Chapters 3 and 4. Readers drawn to numerically grounded solutions to problems (dare we say "engineers"?) will find the algebraic approach a refreshing demonstration of how concepts actually work and are applied, while those with more mathematical thought processes will appreciate the complementary calculus-based models. Either way, the results are similar (and, as I tell my students, it doesn't matter how you learn it)